AGE AND GENDER WITH DEGREE OF HYPERTENSION IN ADULTS AT THE CARDIOLOGY CLINIC OF GOTONG ROYONG HOSPITAL IN SURABAYA - Putu Raka Prema Aristian; Epriyanto Tri Darmadi; Maria Patricia Dian Putri (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background : Hypertension is a condition that blood pressure in a person increases with systolic 140 mmHg and/or diastolic 90 mmHg, either based on clinical measurements or health care facilities. Hypertension is often called a "silent killer". Risk factors associated with the incidence of hypertension include age and gender. Goals : To examine the correlation between age and degree of hypertension in adults and the correlation between gender and degree of hypertension in adults at the Cardiology Clinic of Gotong Royong Hospital in Surabaya.Method : This research used an analytical observational method with a cross-sectional design. Data accumulation was obtained through medical records from the Cardiology Clinic of Gotong Royong Hospital in Surabaya. This research used simple random sampling as the sampling technique. Meanwhile, the expected analysis results from this research are p-value ≤ 0.05 and r value = 0.8 – 1.00.Result : The result of analysis after the Spearman test about the correlation between age and degree of hypertension in adults at the Cardiology Clinic of Gotong Royong Hospital in Surabaya this research found p value = 0.938 which is interpreted as a non-significant correlation and r value=   -0.012, which is interpreted as a very weak correlation. Then, the result of the analysis of the correlation between gender and degree of hypertension in adults at the Cardiology Clinic of Gotong Royong Hospital in Surabaya had a p-value = 0.632, which is interpreted as a non-significant correlation and an r value = -0.072, which is interpreted as very weak correlation.Conclusion : There is no correlation between age and degree of hypertension in adults, nor between gender and degree of hypertension in adults at the Cardiology Clinic of Gotong Royong in Surabaya.